Analisis Sistem Pengelolaan Limbah B3 di Industri Minuman Ringan Kabupaten Sidoarjo - Rizky Maulida Annisafitri; Pranandito Wisnu Prabowo; Tuhu Agung Rachmanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The purpose of this study is to determine the handling of b3 waste by the soft drink industry. The research method used is to compare the local situation with current regulations. The comparison is carried out using a guttman scale where if it is appropriate, a score of 1 is given and if it is not appropriate, a score of 0 is given. The source of B3 waste generated by the soft drink industry comes from maintenance activities, laboratories, offices, and transportation. The type of hazardous waste comes from category 1 general specific sources, namely expired chemicals from laboratories, while from non-specific sources in the form of hazardous contaminated waste, waste from laboratories containing hazardous substances, and used batteries. Then there are category 2 general specific sources in the form of used toner, while from non-specific sources in the form of electronic waste, used B3 packaging, used cloth, used lubricating oil, and residual ink. The characteristics of B3 waste produced include toxic, flammable, and corrosive. In the transportation of B3 waste, the Sidoarjo Regency Soft Drink Industry has collaborated with third parties. Based on the results of the analysis of B3 waste management in soft drink industry companies classified in the “good” category. However, there are still things that need to be improved in the management of B3 waste in the form of applying symbols and labels, packaging, and storage.